2022
DOI: 10.1002/ijgo.14437
|View full text |Cite
|
Sign up to set email alerts
|

Kin17 high expression as a potential biomarker for high‐grade cervical intraepithelial neoplasia

Abstract: This analysis was partially funded from the CDC, which also provided technical assistance related to analysis and interpretation of data and writing the report (contract 75D30120C08186). The findings and conclusions in this report are those of the authors and do not necessarily represent the official position of the CDC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…Of note, a recent study found that the expression level of KIN17 was positively associated with the severity of cervical lesions, indicating that KIN17 is a novel protein biomarker for high-grade CIN (62). High-grade CIN is considered to be the precursor of cervical carcinoma, which further suggests that KIN17 may be used as a predictive biomarker for cervical cancer.…”
Section: Roles Of Kin17 In Cancer Cellsmentioning
confidence: 99%
“…Of note, a recent study found that the expression level of KIN17 was positively associated with the severity of cervical lesions, indicating that KIN17 is a novel protein biomarker for high-grade CIN (62). High-grade CIN is considered to be the precursor of cervical carcinoma, which further suggests that KIN17 may be used as a predictive biomarker for cervical cancer.…”
Section: Roles Of Kin17 In Cancer Cellsmentioning
confidence: 99%